Study of prosthetic heart valve thrombosis and outcomes after thrombolysis - Patil, Shivanand; Setty, Natraj; Ramalingam, Rangaraj; Bedar Rudrappa, Mahesh Murthy; Manjunath, Cholenahally Nanjappa (International Journal of Research in Medical Sciences, 2019)
Background: The study aimed to evaluate the clinical presentation, diagnostic features, treatment strategies, and complications of prosthetic heart valve thrombosis (PHVT) and to determine efficacy, outcomes and complications of thrombolytic therapy during hospital stay. Methods: This was a prospective, observational, single-centre study carried out between March, 2016 and December, 2017 at a tertiary care centre in India. Total 110 patients with history of prosthetic heart valve replacement and symptoms related to PHVT were included in the study. Patients underwent thrombolysis, surgery or conservative management for treatment of PHVT, as per their individual clinical presentation. Clinical profile and treatment outcomes were assessed using a pre-tested, semi-structured questionnaire and clinical assessment. Results: Mean age of the patients was 39.4±12.5 years. Most of the patients presented with NYHA class II and III (85.4%) symptoms. Total 20.9% of patients were poorly compliant with anticoagulants. Thrombolysis was initial treatment in 105 (95.5%) patients. Five (4.6%) patients were treated with heparin. Two patients underwent surgery after failed thrombolysis. Mortality in the thrombolysis group was 6.6%. Embolism occurred in 8.6% of the group and major bleeding in 1.9%. One patient who underwent surgery died. Conclusions: In light of these results, it can be concluded that most cases of PHVT are due to inadequate anticoagulation and poor monitoring mainly in patients belonging to the lower socioeconomic group. Thrombolysis can be considered as first line therapy where the immediate surgical options are remote.